The Fulfillment of Parties' Election Pledges: A Comparative Study on the Impact of Power Sharing. Issue 3 (6th June 2017) - Thomson, Robert; Royed, Terry; Naurin, Elin; Artés, Joaquín; Costello, Rory; Ennser‐Jedenastik, Laurenz; Ferguson, Mark; Kostadinova, Petia; Moury, Catherine; Pétry, François; Praprotnik, Katrin
Abstract: Why are some parties more likely than others to keep the promises they made during previous election campaigns? This study provides the first large‐scale comparative analysis of pledge fulfillment with common definitions. We study the fulfillment of over 20, 000 pledges made in 57 election campaigns in 12 countries, and our findings challenge the common view of parties as promise breakers. Many parties that enter government executives are highly likely to fulfill their pledges, and significantly more so than parties that do not enter government executives. We explain variation in the fulfillment of governing parties' pledges by the extent to which parties share power in government. Parties in single‐party executives, both with and without legislative majorities, have the highest fulfillment rates. Within coalition governments, the likelihood of pledge fulfillment is highest when the party receives the chief executive post and when another governing party made a similar pledge.